Cross-linkable Fullerene Derivatives for Solution-processed n–i-p Perovskite Solar Cells - Wojciechowski, K; Ramirez, I; Gorisse, T; Dautel, O; Dasari, R; Sakai, N; Martinez Hardigree, J; Song, S; Marder, S; Riede, M; Wantz, G; Snaith, H (American Chemical Society, 2016)
Hybrid perovskites form an extremely attractive class of materials for large scale, low-cost photovoltaic applications. Fullerene-based charge extraction layers have emerged as a viable n-type charge collection layer, and in “inverted” p–i–n device architectures the solar cells are approaching efficiencies of 20%. However, the regular n–i–p devices employing fullerenes still lag behind in performance. Here, we show that partial solubility of fullerene derivatives in the aprotic solvents used for the perovskites makes it challenging to retain integral films in multilayer solution processing. To overcome this issue we introduce cross-linkable fullerene derivatives as charge collection layers in n–i–p planar junction perovskite solar cells. The cross-linked fullerene layers are insolubilized and deliver improved performance in solar cells enabled by a controllable film thickness.